Development of LKPD Based on Contextual Teaching and Learning on Square and Rectangular Materials to Improve Learning Outcomes of Grade IV Elementary School Students - Oktapia, Lisa; Siregar, Lailatun Nur Kamalia (Universitas Wiralodra, 2023)
Student Worksheets (LKPD) are one of the teaching materials that play an important role in the learning process. In the data structure of mathematics subjects, LKPD is CTL-based with square and rectangular shapes. This research was conducted on grade IV students of SDN 106161 Laut Dendang. Elementary school students in the fourth grade were used as research participants. This study uses an analysis, design, development, implementation, and evaluation (ADDIE) model. The results of this study can be seen and proven by using the Likert scale to assess the material and aspects that are still being developed, namely: a) Validity that gets a score (4.8) from media experts and (4.43) from experts in materials. b) Efficiency, i.e. obtaining a score of 3.96 from students and 4.6 from teachers. c) Fairness of use of estimated N-Gain reaches value 0.8110. The study's findings, students' enthusiasm in learning math about square and rectangular shapes should be made easier for educators and prospective teachers. In addition, this development is expected to help students gain a deeper understanding of the subject matter they are learning, thereby increasing their interest in CTL-based LKPD exercises.